Evaluation of Psychotherapy through a Monitoring System - Ljubotina, Damir (Array, 2003)
The paper describes concepts, and issues related to process of evaluation of psychotherapeutic interventions. Theoretical rationale and practical issues in data collection procedures are given, and the basic elements of the evaluation process are stated and discussed.